Desenvolvimento de ligas de alumínio nanoestruturadas para a utilização em cabos elétricos - PRAZERES, Emerson Rodrigues (Universidade Federal do Pará, 2023)
Aluminum nanocomposites demonstrate the ability to improve mechanical properties, thermal and electrical conductivity. For aluminum, the incorporation of multi-walled carbon nanotubes (NTCPM) using conventional melting methods is an old problem, due to disintegration of the walls of carbon nanotubes when subjected to high temperatures. In this study, aluminum nanocomposites were manufactured by the conventional casting method, using stainless steel powder (304LSS), nanostructured silicon and nickel. The carbon nanotubes were treated with hydrogen peroxide, allowing adhesion by polar interaction with the particles of the metallic powders. The nanostructured compounds were added to the aluminum matrix by means of conventional casting. After obtaining the material as a melt, it went through the machining process to a diameter of 18.5 mm and then through the cold working process until a diameter of 3.0 mm was obtained. The alloys were characterized mechanically through tensile and microhardness tests, electrically through electrical resistance tests, using a 2-point kelvin bridge, and structurally through macrostructure and microstructure analyses. The 304LSS powder added alloying elements, refined the grains and the NTC improved electrical conductor performance, with electrical conductivity gains in the range of 10%. Associates associated with carbon-associated components not linked to chains of protein chains are compounds of carbon, associated with proteins, aggregates, associated with carbon, associated with proteins, associated with significant proteins in the LRT. The alloys with Ni and carbon nanotubes contributed to significant gains in electrical conductivity and LRT, with the alloy with 2% nickel and 0.1% NTC showing gains of approximately 8% in electrical and mechanical properties. Nanostructured alloys were also superior in terms of electrical and mechanical properties than commercial alloys.